The Adventures of Old Mr. Toad - Burgess, Thornton W. (Thornton Waldo), 1874-1965; Cady, Harrison, 1877-1970 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Adventures of Old Mr. Toad" by Thornton W. Burgess is a children's book written in the early 20th century. This engaging narrative focuses on the life of Old Mr. Toad and his various adventures, set within the backdrop of nature and its inhabitants. The book taps into themes of friendship, self-discovery, and the importance of humility, particularly through the character of Old Mr. Toad, who learns valuable lessons about pride and respect for others. The story begins with Old Mr. Toad hastily making his way to join others for a spring chorus at the Smiling Pool. Along the way, his friends, including Jimmy Skunk and Peter Rabbit, become curious about his sudden urgency and the claim of his beautiful singing voice. As the tale unfolds, Old Mr. Toad's character evolves with humorous encounters and lighthearted dialogue, building a rich depiction of life in the meadow. Through adventures involving his babies, confrontations with predators like Mr. Blacksnake, and lessons learned about pride after dining with Buster Bear, Old Mr. Toad ultimately discovers the value of friendship and humility. The charming illustrations that accompany the story further enhance its appeal to young readers, making it a delightful exploration of nature and character growth. (This is an automatically generated summary.)
Release date is 2004-06-01
Produced by David Newman and PG Distributed Proofreaders
Keywords: Animals -- Juvenile fiction; Rabbits -- Juvenile fiction; Toads -- Juvenile fiction